2022
DOI: 10.1101/2022.10.06.511140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Escalation of alcohol intake is associated with regionally decreased insular cortex activity but not associated with changes in taste quality

Abstract: Background: Intermittent access to ethanol (EtOH) drives persistent escalation of intake and rapid transition from moderate to compulsive-like drinking. Intermittent EtOH drinking may facilitate escalation in part by altering aversion-sensitive neural substrates, such as the insular cortex (IC), thus driving greater approach toward stimuli previously treated as aversive. Methods: We conducted a series of experiments in rats to examine behavioral and neural responses associated with escalation of EtOH intake. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…We found that EtOH-exposed rats had a near complete loss of responding to the aversive orosensory properties of EtOH (20%) as well as significantly reduced neural activation within the posterior IC, relative to EtOH-naïve controls. Furthermore, the number of elicited aversive-associated TR responses was positively correlated with the amount of Fos-like immunoreactivity in the posterior IC (Mukherjee et al, 2023). Within the present study, ibotenic acid lesions were targeted toward an area just slightly rostral to those more posterior regions (~0.3 mm posterior to bregma) in which we found these previous Fos-behavior associations.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…We found that EtOH-exposed rats had a near complete loss of responding to the aversive orosensory properties of EtOH (20%) as well as significantly reduced neural activation within the posterior IC, relative to EtOH-naïve controls. Furthermore, the number of elicited aversive-associated TR responses was positively correlated with the amount of Fos-like immunoreactivity in the posterior IC (Mukherjee et al, 2023). Within the present study, ibotenic acid lesions were targeted toward an area just slightly rostral to those more posterior regions (~0.3 mm posterior to bregma) in which we found these previous Fos-behavior associations.…”
Section: Discussionsupporting
confidence: 50%
“…Subsequently, the posterior IC is then thought to relay these signals to the anterior IC, where they may reach conscious awareness and undergo memory consolidation (Droutman et al, 2015). We have previously demonstrated a correlation between reduced IC activation and a loss of responding to the aversive orosensory properties of EtOH that naturally develop following repeated EtOH drinking sessions (Mukherjee et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations